INNV-27. THE IMPACT OF A DEDICATED MULTIDISCIPLINARY TUMOR BOARD ON CARE FOR PATIENTS WITH BRAIN METASTASES. (11th November 2019) - Wang, Nancy; Cohen, Justine; Goss, Nathaniel; Bertalan, Mia; Keeley, Maura; Parsons, Michael; Nahed, Brian; Cahill, Daniel; Oh, Kevin; Brastianos, Priscilla
Abstract: : Brain metastases (BM) are the most common tumors to affect the central nervous system (CNS). Treatment options have recently evolved with the use of new targeted therapies, immune checkpoint inhibitors, and increased access to clinical trials. We describe our institutional experience with a weekly tumor board dedicated to BM. METHODS: We conducted a single-institution cohort study at an academic hospital. Attendance at tumor board included representatives from neuro-oncology, medical oncology, radiation oncology, neurosurgery, neuropsychology, and neuroradiology. We prospectively gathered data on patient demographics, clinical history, and tumor board recommendations. Patients were followed to assess treatment course and survival. The Kaplan Meier method was used to calculate time to progression. RESULTS: A total of 49 patients were presented over 2 months. The median age at presentation was 63 yrs with a median ECOG of 1. The primary malignancy was 35% melanoma, 29% lung, 23% breast, the remainder other. Most patients had advanced, heavily pretreated disease: 69% had Stage IV disease with a median of 2 prior lines of systemic therapy, 73% had multiple BM, 39% had prior surgical resection of BM, and 57% had prior CNS radiation. Change in management was recommended in 26/53 case presentations, with active BM-directed therapy (surgery, radiation, systemic therapy) recommended in 25/26 patients. The median time to start active therapy was 7 days. Only 3 patients have died at a median follow-up of 62 days. 9 patients have progressed, with a median time to progression of 57 days. CONCLUSIONS: Multidisciplinary BM tumor board provides unique opportunities in the management of complex BM patients in an era of rapidly evolving therapeutic options. Additional follow-up is needed to assess long-term outcomes.